Διαπολιτισμική Εκπαίδευση – Σκέψεις και κριτικές επισημάνσεις για το «αντικείμενο» της αναγνώρισης - Γκόβαρης, Χρήστος (Παιδαγωγικά ρεύματα στο Αιγαίο, 2024)
The question "how to realize the goal of recognizing and acknowledging cultural differences, while avoiding the risk of reproducing stereotypes about the 'other'?" remains of major importance for the theory and practice of Intercultural Education. This question requires clarification regarding "how" exactly we conceptualize "recognition" and, respectively, define its "object". Starting from these findings, this paper deals, in a first step, with three main conceptualizations of recognition by Taylor, Honneth & Stojanov, and by Butler, examining "how" in each case the "object" of recognition and, by extension, the goal of the subject's educational process is defined. In a second step, an attempt is made to correlate the theoretical conclusions with the perspective of the recognition needs of adolescents with an immigrant background, in order to clarify that conceptualization of recognition which can meet both the needs of the subjects and the critical and emancipatory character of Intercultural Education. We conclude that the definition of the "object" of recognition in the case of adolescents with an immigrant background should have as its central reference point their efforts to form a culturally pluralistic self, through the overcoming of social distinctions and separations caused by the dominant ethnic discourse.